Hubungan Antara Pengetahuan Wanita Usia Subur Tentang Kanker Serviks dan Tindakan Pemeriksaan Pap Smear di Kelurahan Sidanegara Kabupaten Cilacap - Annisa, Winda Nur (2016)
Background: Cervical cancer occupies the highest mortality rates among other types of cancer among women. The inspection pap smear contimay facilitate the diagnosis and management of cervical cancer. Objective: This researchis to analyze there is a relationship between knowledge of women childearing ageabout cervical cancer and pap smear examination in Sidanegara Cilacap. Methods: The research desain that used isobservational analytic methodwith cross sectional approachment in December2015 in the Sidanegara Village Cilacap. Thesize ofsample44samples. Sampling using purposive sampling technique. Data were analyzed using Fisher test using SPSS 20.0 program for windows. Result of Research: There isa significant relationship between knowledge of reproductive age women about cervical cancer with a Pap Smear examination with the test results obtained by the Fisher Exact Test p value of 0.000. Respondents were knowledge well as much as33respondents, 78.8% of them choose a Pap smear while the remaining21.2% did not pap smears. Respondents were bad knowledgeas many as 11respondents, only one respondent who perform pap smears, it show link ages to the knowledge of good and bad actions pap smears. Conclusions: There is a significantrelationship between knowledge of reproductive age women about cervical cancer and Pap smear examination in Sidanegara Village Cilacap Distrct.